The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.11.04.368779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Advanced Biophysical Model to Capture Channel Variability for EQS Capacitive HBC

Abstract: Human Body Communication (HBC) has come up as a promising alternative to traditional radio frequency (RF) Wireless Body Area Network (WBAN) technologies. This is essentially due to HBC providing a broadband communication channel with enhanced signal security in the physical layer due to lower radiation from the human body as compared to its RF counterparts. An in-depth understanding of the mechanism for the channel loss variability and associated biophysical model needs to be developed before EQS-HBC can be us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…At lower distances and when the ground electrodes of the transmitter and receiver are parallel, the inter-device coupling capacitor, , is higher (See Figure 18 ). Higher results in a part of the signal returning through instead of through the relatively high impedance path and improving the channel quality [ 107 ]. Again, applications generally dictate the locations and orientations for the transmitter and receiver ground electrodes; meaning, the options to increase is limited.…”
Section: Human Body Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…At lower distances and when the ground electrodes of the transmitter and receiver are parallel, the inter-device coupling capacitor, , is higher (See Figure 18 ). Higher results in a part of the signal returning through instead of through the relatively high impedance path and improving the channel quality [ 107 ]. Again, applications generally dictate the locations and orientations for the transmitter and receiver ground electrodes; meaning, the options to increase is limited.…”
Section: Human Body Communicationmentioning
confidence: 99%
“…Circuit element models the resistance of the conductive core of the body. Circuit element represents the inter-device coupling capacitance between the ground electrodes of and [ 107 ]. Parallel combination of resistance, , and capacitance, , model the termination impedance [ 106 ].…”
Section: Figurementioning
confidence: 99%
“…Bio-physical models for C-HBC were developed in our earlier works 18,34 where the effects of these capacitances on the overall channel transfer function were analyzed, which was found to be proportional to the return path capacitances at both the TX and the RX. The effect of moving the TX device within the body (for an implant) was also analyzed 18 , which showed that the return path capacitance for the implanted TX becomes almost zero, as the electric fields terminate within the body, and cannot terminate to the earth's ground as in the wearable scenario. Due to the absence of a TX return path capacitance, the RX received voltage becomes zero.…”
Section: Pros and Cons Of Capacitive Eqs Hbc (C-hbc) For Brain Implantsmentioning
confidence: 99%
“…Two differential metal electrodes attached to the sides of the bowl work as the RX electrodes, which are connected to a TI BUF602 buffer configured as a 50 Ω driver for measurement instruments. The TI buffer offers ~2 pF capacitive termination at the input of the RX, which helps in establishing a wideband HBC channel as shown in earlier works 18,31,33,34 The mouse was anaesthetized with 2-3% isoflurane throughout the surgery. After shaving the hair, the animal was fixed on a stereotaxic frame, so that the head does not move during the experiment, and the head skin was sterilized.…”
Section: /20mentioning
confidence: 99%
See 1 more Smart Citation